Jiang Zemin’s ideas of «three representatives» - Batpenova, Z. S.; Abilekova, G. K. (Journal of Oriental Studies, 2016)
This article discusses the value and importance of the significant project in the history of the Communist Party of China – the idea of «Three Represents» of Jiang Zemin.